Keterlibatan Ninik Mamak Dalam Penyelesaian Konflik Sosial Pada Masyarakat Di Dusun Tanah Tumbuh - Joko Setyoko; Ronal Dison; Winda Nasmarita (Jurnal Politik dan Pemerintahan Daerah, 2025)
This study aims to examine the involvement of ninik mamak (traditional elders) in Dusun Tanah Tumbuh in resolving social conflicts. The research was motivated by the frequent occurrence of social conflicts in Dusun Tanah Tumbuh. The method used in this study is a descriptive method with a qualitative approach. The technique used to select informants is purposive sampling (a sampling method based on specific considerations). Data collection techniques include observation, interviews, and documentation. The results of the study show that the solutions offered by the ninik mamak of Dusun Tanah Tumbuh to resolve social conflicts involve two main methods: mediation and customary court hearings. The ninik mamak have fulfilled their role as enforcers of customary law in accordance with prevailing customary regulations. This role is evidenced by their direct involvement in customary court proceedings and their recommendations in the decision-making process. Another role played by the ninik mamak is acting as intermediaries or mediators in conflict resolution. The challenges faced by the ninik mamak in resolving social conflicts include non-compliance from disputing parties during both mediation and customary court processes, dissatisfaction with the outcomes of these processes, and a lack of public understanding regarding customary court procedures, which often leads to public debate and controversy.